(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2021)
The authors examine animal welfare indicators for the bovine species, with particular reference to dairy cow. This work proposes a practical approach to the Functional Area of Animal Health, considers the issue of animal welfare as an integrated concept, the current legislation –horizontal and vertical-, the epidemic surveillance system (Classyfarm) and biosecurity in breeding.